2013
DOI: 10.1371/journal.pone.0076025
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone Protected Human Brain Microvascular Endothelial Cells from Methylglyoxal-Induced Injury by Inhibiting AGEs/RAGE/Oxidative Stress

Abstract: Subjects with diabetes experience an increased risk of cerebrovascular disease and stroke compared with nondiabetic age-matched individuals. Increased formation of reactive physiological dicarbonyl compound methylglyoxal (MGO) seems to be implicated in the development of diabetic vascular complication due to its protein glycation and oxidative stress effect. Edaravone, a novel radical scavenger, has been reported to display the advantageous effects on ischemic stroke both in animals and clinical trials; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 30 publications
8
44
0
1
Order By: Relevance
“…We could see a concentration-and time-dependent effect based on kinetic data from impedance measurements. Our data are in agreement with viability studies on the effect of edaravone pretreatment against methylglyoxal-induced toxicity (Li et al, 2013c).…”
Section: Protection By Edaravonesupporting
confidence: 91%
See 4 more Smart Citations
“…We could see a concentration-and time-dependent effect based on kinetic data from impedance measurements. Our data are in agreement with viability studies on the effect of edaravone pretreatment against methylglyoxal-induced toxicity (Li et al, 2013c).…”
Section: Protection By Edaravonesupporting
confidence: 91%
“…Elevated level of ROS weakens the barrier integrity , however the contribution of methylglyoxaltriggered ROS production in the increased endothelial permeability is controversial (Li et al, 2013b). In the present study we confirmed that methylglyoxal treatment promotes oxidative stress in brain endothelial cells, similarly to previous results on endothelial cells (Li et al, 2013b;Li et al, 2013c) and other cellular systems . The kinetics of ROS production helped to determine the optimal time point for protection assays and other experiments: the 4 h time point, where ROS formation was still elevated, was purposefully selected.…”
Section: Methylglyoxal Induced Changes In Brain Endothelial Cellssupporting
confidence: 91%
See 3 more Smart Citations